Intestinal gas homeostasis: disposal pathways. Issue 3 (4th January 2015) - Mego, M.; Bendezú, A.; Accarino, A.; Malagelada, J.‐R.; Azpiroz, F.
Abstract Background Patients with functional gut disorders frequently complain of gas‐related symptoms, but the role of intestinal gas in this context is not clear, because intestinal gas homeostasis is incompletely understood. Our aim was to compare the proportion of the gas produced by colonic fermentation that is evacuated per anus and that eliminated via alternative pathways. Methods In 20 healthy subjects, gas evacuated per anus was collected for 4 h after a standard flatulogenic test meal. Paired studies were performed without and with high‐rate infusion of exogenous gas (24 mL/min) into the jejunum to wash‐out of the gut the endogenous gas produced by bacterial fermentation. The exogenous gas infused was labeled (5% SF6) to calculate the proportion of endogenous gas evacuated. Key Results In the experiments with gaseous wash‐out, 1817 ± 139 mL of endogenous gas was produced over the 4‐h study period. However, in the experiments without wash‐out (basal conditions), 376 ± 43 mL were evacuated, indicating that only 23 ± 3% of the gas produced was finally eliminated per anus, while the rest (77 ± 3%) had been previously eliminated via alternative pathways. Conclusions & Inferences Intestinal gas homeostasis is a highly dynamic process by which a large proportion of the gas produced by bacterial fermentation of meal residues is rapidly absorbed into the blood and/or metabolized by gas‐consuming microorganisms, and only a relatively modest proportion is eliminated per anus. These data contribute to clarify the complex dynamics of intestinal gas and may help interpret the pathophysiology of gas‐related symptoms.